Evolution of kink bands in a notched unidirectional carbon fibre-epoxy composite under four-point bending. (1st March 2019) - Wang, Ying; Chai, Yuan; Soutis, Costas; Withers, Philip J.
Abstract: Kink-band nucleation and propagation has been monitored over time in three dimensions (3D) by time-lapse X-ray computed tomography (CT) in the compressive zone of a blunt notched unidirectional (UD) T800 carbon fibre/epoxy composite under in situ four-point bending (FPB). The kink bands that develop from micro-buckling are classified into two types, namely type 1 and type 2 by analogy with Euler buckling. Type 1 (shear) kink bands accommodate a lateral displacement of the fibres either side of the kink band; whereas type 2 kinks comprise conjugate pairs forming chevrons (accompanied by a tilt if the bands are wedge-shaped). In the central plane of the sample the kink bands lie in the plane of bending, whereas near the side surfaces the lack of lateral constraint means that type 2 kink band pairs protrude out of the surface (normal to the bending plane) from the notch corners down the sides of the sample. Moreover, a comparison of CT scans during loading and after unloading shows that geometries measured post-mortem on cross-sections may not be wholly representative, with the angle of the broken fibre segments within the kink bands reduced by 10–20° and the curvature of buckled fibres almost halved. The novelty of this work relates to the observation of the nucleation and propagation of fibre kink bands in three dimensions and the definition and quantification of kink band variables that could lead to more accurate modelling and simulation of compressive behaviour.